Despicable me 4 [videorecording (DVD)] - White, Mike, 1970-; Daurio, Ken; Williams, Pharrell (Universal, 2024)
Gru, the world's favorite supervillain-turned-Anti-Villain League-agent, returns for an exciting, bold new era of Minions mayhem. Gru and Lucy and their girls Margo, Edith, and Agnes, welcome a new member to the Gru family, Gru Jr., who is intent on tormenting his dad. Gru faces a new nemesis in Maxime Le Mal and his femme fatale girlfriend Valentina, and the family is forced to go on the run.